Enhancing Methane Production from Lignocellulosic Waste through Optimized Operational Strategies in Anaerobic Co-Digestion: Cotton Stalks as a Case Study - Sharaby, Esraa G.; EL-Hadidi, Yasser M.; Nasrallah, Nasser A. (Journal of Neonatal Surgery, 2024)
Cotton stalks (CS) are a lignocellulosic biomass that pose challenges for anaerobic digestion (AD) due to their high lignin content, which leads to long digestion periods, inhibits hydrolysis, limits biodegradability, and produces low methane yields. One successful method to overcome these limitations is co-digestion, which involves mixing cotton stalks with different substrates. For this reason, a thermostatic stainless-steel water bath and a ten-batch system of biodigesters were designed, established, and implemented at the Biochemistry Laboratory, Water and Soil Science Department, Faculty of Technology and Development, Zagazig University (Egypt). Azolla (AZ) and cow manure (CM) were used for different mixing ratios with cotton stalks to evaluate how different substrate mixtures influence biogas production and its methane content. Ten experimental mixtures were conducted: mixture1 (100% CS), mixture2 (100% CM), mixture3 (100% AZ), mixture4 (75% CS + 25% CM), mixture5 (50% CS + 50% CM), mixture 6 (25% CS + 75% CM), mixture7 (75% CS + 25% AZ), mixture8 (50% CS + 50 % AZ), mixture 9 (25% CS + 75% AZ) and mixture10 (CS:CM:AZ = 1:1:1). Experiments were performed under controlled conditions with daily biogas measurements and methane concentration, calorific value estimation, and chemical analysis of influent and effluent throughout digestion. Notably, mixture 10 yielded superior biogas production compared to mixtures 1 through 9, with increases of 56.13%, 35.92%, 43.45%, 32.21%, 21.65%, 21.12%, 13.54%, and 7.91%, respectively, except for mixture 3, which exceeded it by 13.85%. Among all mixtures, mixture 3 showed the highest methane concentration, while others ranged between 37.85% and 71.49%. The statistical analysis of both cumulative biogas and methane production showed a highly significant effect at p < 0.001. The R² reached 1.0 for cumulative biogas production and 96.9% for methane production, indicating clear and well defined differences among the treatments